Surface-Modified Bilosomes Nanogel Bearing a Natural Plant Alkaloid for Safe Management of Rheumatoid Arthritis Inflammation - Mohammed H. Elkomy; Nabil K. Alruwaili; Mohammed Elmowafy; Khaled Shalaby; Ameeduzzafar Zafar; Naveed Ahmad; Izzeddin Alsalahat; Mohammed M. Ghoneim; Essam M. Eissa; Hussein M. Eid (MDPI AG, 2022)
Rheumatoid arthritis (RA) is a chronic inflammatory illness affecting the joints. The characteristic of RA is gradual joint deterioration. Current RA treatment alleviates signs such as inflammation and pain and substantially slows the progression of the disease. In this study, we aimed to boost the transdermal delivery of berberine (a natural product) by encapsulating it in chitosan, surface-modified bilosomes nanogel for better management of the inflammation of RA. The chitosan-coated bilosomes loaded with berberine (BER-CTS-BLS) were formulated according to the thin-film hydration approach and optimized for various causal variables, considering the effect of lipid, sodium deoxycholate, and chitosan concentrations on the size of the particles, entrapment, and the surface charge. The optimized BER-CTS-BLS has 202.3 nm mean diameter, 83.8% entrapment, and 30.8 mV surface charge. The optimized BER-CTS-BLS exhibited a delayed-release profile in vitro and increased skin permeability ex vivo. Additionally, histological examination revealed that the formulated BLS had no irritating effects on the skin. Furthermore, the optimized BER-CTS-BLS ability to reduce inflammation was evaluated in rats with carrageenan-induced paw edema. Our results demonstrate that the group treated with topical BER-CTS-BLS gel exhibited a dramatic reduction in rat paw edema swelling percentage to reach 24.4% after 12 h, which was substantially lower than other groups. Collectively, chitosan-coated bilosomes containing berberine have emerged as a promising therapeutic approach to control RA inflammation.